Psychometric Evaluation of the Arabic Version of the Fear of COVID-19 Scale - Alyami, Mohsen (Int J Ment Health Addict, 2020)
Fear is a central emotional response to imminent threats such as the coronavirus-19 disease (COVID-19). The Fear of COVID-19 Scale (FCV-19S) assesses the severity of fear towards COVID-19. The present study examined the psychometric properties of the Arabic version of the FCV-19S. Using a forward-backward translation, the FCV-19S was translated into Arabic. An online survey using the Arabic versions of FCV-19S and the Hospital Anxiety and Depression Scale (HADS) was administered. Reliability and concurrent and confirmatory validity were examined. The dataset consisted of 693 Saudi participants. The internal consistency of the Arabic FCV-19S was satisfactory (α = .88), with sound concurrent validity indicated by significant and positive correlations with HADS (r = .66). The unidimensional structure of the FCV-19S was confirmed. The Arabic version of the FCV-19S is psychometrically robust and can be used in research assessing the psychological impact of COVID-19 among a Saudi adult population.